From fire, by water : my journey to the Catholic faith - Ahmari, Sohrab (Ignatius Press, 2019)
Sohrab Ahmari was a teenager living under the Iranian ayatollahs when he decided that there is no God. Nearly two decades later, he would be received into the Roman Catholic Church. In From Fire, by Water, he recounts this unlikely passage, from the strident Marxism and atheism of a youth misspent on both sides of the Atlantic to a moral and spiritual awakening prompted by the Mass. At once a young intellectual's finely crafted self-portrait and a life story at the intersection of the great ideas and events of our time, the book marks the debut of a compelling new Catholic voice.